2013
DOI: 10.1002/ppap.201300088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Vapor Addition on the Surface Modification of Polyethylene in an Argon Dielectric Barrier Discharge

Abstract: In this paper, water vapor up to 41% is added to an argon dielectric barrier discharge at medium pressure to profoundly investigate the effect of water vapor addition on the surface modification of polyethylene (PE). Contact angle measurements show that the wettability of PE significantly increases after a pure argon plasma treatment. However, the addition of water vapor to the argon feeding gas can give an extra 30% decrease in water contact angle. This extra decrease is due to the incorporation of additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Plasma treatment of LDPE in an argon DBD was found to reduce the WCA from 101.8° to 51.9° (50% WCA reduction) and an O/C ratio of 13% was obtained at the surface [17]. In a DC low pressure glow air discharge the WCA was found to decrease from 89.5° to 50.7°…”
Section: Influence Of the Distance Between The Capillary And The Foilmentioning
confidence: 90%
“…Plasma treatment of LDPE in an argon DBD was found to reduce the WCA from 101.8° to 51.9° (50% WCA reduction) and an O/C ratio of 13% was obtained at the surface [17]. In a DC low pressure glow air discharge the WCA was found to decrease from 89.5° to 50.7°…”
Section: Influence Of the Distance Between The Capillary And The Foilmentioning
confidence: 90%
“…Up to now, the aging behavior of plasma-treated polymers has only been studied using a single discharge gas. In previous work, it has already been shown that water vapor addition to the argon plasma gas has a beneficial effect on the wettability of the LDPE films [15]. In what follows next, it will be investigated whether the addition of water vapor can also have a positive influence on the aging behavior.…”
Section: Influence Of Water Vapor Addition To the Plasma Gasmentioning
confidence: 96%
“…This may indicate that the polar groups introduced on the surface by Ar/water vapor plasmas remain longer on the surface as the concentration of the oxygen functional groups is higher [15]. XPS measurements can give a better insight in the chemical changes occurring on the plasma-treated surface upon storage and are therefore studied in the next paragraph.…”
Section: Influence Of Water Vapor Addition To the Plasma Gasmentioning
confidence: 98%
See 2 more Smart Citations